Meemo: desenvolvimento de uma aplicação móvel voltada ao controle de finanças pessoais. - Vale, Lívian Almeida Chaves do (Brasil, 2022)
This academic work documents the process of developing a prototype for a mobile application aimed at controlling personal finances. This artifact was built from the methodology guided by the CBL (Challenge Based Learning) framework (Nichols, 2016). Where we tried to explore concepts of Psychology applied to user experience (UX) during all phases of the research, having the approach as its main objective. The project sought to develop low and medium fidelity navigable prototypes, including validation steps with users from interviews and usability tests. At the end of the process, a high-fidelity prototype of the flows that embraced its first version of MVP (Minimum Viable Product) was obtained. The final result consists of interfaces for this alternative, where user-centered concepts studied can be applied.